The effect of Ag on thermoelectric performance of Cu1-xAgxS tetrahedrite/Al prepared using modified polyol methods. (June 2020) - Aditya, D; Rizky, A S; Suprayogi, T; Yogihati, C I; Diantoro, M; Sunaryono; Said, S M
Abstract: In principle, thermoelectric technology is a semiconductor which capability to convert thermal energy into electrical energy. We used Ag-doped CuS deposited on aluminum foil as a sample understudied. The Cu1-x Agx S was prepared using a modified polyol method. Firstly, CuS powder was dissolved together with dopant using TEG (TetraEthylene Glycol) and NaBH4 with nitrogen, heated at 200 °C, and followed by centrifuged at 5000 rpm. The Characterization of CuS was carried out using XRD, SEM, and I-V. It is shown that the electrical conductivity tends to increase with increasing the Ag dopant. The highest electrical conductivity was reached at 70 °C. We also found that the crystallinity enhanced with the addition of Ag into CuS. Meanwhile, morphological inspection revealed that the increase of Ag, causing changes in grain shape.